DESIGN OF 3,36 MWP FLOATING PHOTOVOLTAIC POWER PLANT IN MRICA RESERVOIR - Irvan Fauzi, Mohammad
The design of a 3.36 MWp floating PLTS in the Mrica hydropower reservoir is carried out by considering the profile of the Mrica hydropower reservoir, technical design, technical analysis, economics, and the environment of the floating photovoltaic power plant. Floating PLTS system with a capacity of 3.36 MWp was established with a pontoon-based floating type with an HDPE type floater. The floating PLTS system consists of 281 strings with the number of PV modules installed is 6,108 modules with an azimuth of 0° and a tilt angle of 10°. Trina Solar TSM-550DE19 PV module with a capacity of 550 Wp and Huawei SUN2000-100KTL-M1 with a capacity of 100 kW and total 27 inverters are used for the design. The total surface area of the Mrica reservoir required by the floating photovoltaic power plant is 32,556 m2 . The energy produced in the first year was 4,965 MWh, specific energy yield was 1,478 kWh/kWp, and a performance ratio of 82.39%. The energy output of the floating photovoltaic power plant system is connected to GI 150 kV Mrica hydropower. From the economic aspect, several results of economic calculations were obtained. The LCOE of the floating photovoltaic power plant system is Rp. 857.6/kWh, the IRR is 11.97%, the NPV is Rp. 19.267.415,074 and the payback period is 9.46 years. The floating PLTS system can reduce greenhouse gas emissions by 97,899 tons of CO2 over 25 years. Overall, the floating PLTS system with a capacity of 3.36 MWp in the Mrica hydropower reservoir is feasible to build because it meets several indicators from technical, economic, and environmental aspects.